2003
DOI: 10.1177/107769900308000202
|View full text |Cite
|
Sign up to set email alerts
|

Media Credibility Reconsidered: Synergy Effects between On-Air and Online News

Abstract: This experimental investigation of media credibility examined the combined, or synergistic, effects of on-air and online network news exposure, placing student and adult news consumers in broadcast news, online news, and telewebbing conditions. Results indicate that perceptions of network news credibility are affected by channel used. Perceptions of credibility were enhanced when the channel used was consistent with the news source being evaluated, suggesting a channel congruence effect. In addition, evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
2
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 2 publications
4
119
2
13
Order By: Relevance
“…The notion of incongruence between a preferred media channel and the channel actually used is not unusual. Bucy (2003) and Westley and Severin (1964a) both referenced similar findings in their respective studies. Bucy (2003) found that adults and college students rated media channels with which they were less familiar as more credible.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The notion of incongruence between a preferred media channel and the channel actually used is not unusual. Bucy (2003) and Westley and Severin (1964a) both referenced similar findings in their respective studies. Bucy (2003) found that adults and college students rated media channels with which they were less familiar as more credible.…”
supporting
confidence: 79%
“…Bucy (2003) and Westley and Severin (1964a) both referenced similar findings in their respective studies. Bucy (2003) found that adults and college students rated media channels with which they were less familiar as more credible. Additionally, Westley and Severin (1964a) reported that "residents did not necessarily assign greatest credibility to the medium they assigned greatest preference" (p. 326).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…For message credibility typical variables are that the text is factual, well-written, and fair, and for source credibility variables typically being used are that the source is objective, biased/unbiased, and the source separates facts from opinions (Bucy, 2003;Chung, Kim, & Kim, 2010;Newhagen & Nass, 1989;Sundar, 1999). The study at hand follows in this tradition and emphasizes the effect of transparency on source and message credibility (for a complete list of all variables in the study see the results section).…”
Section: Methodsmentioning
confidence: 99%
“…No obstante, se hallaron resultados similares a los encontrados por Busy (2003), donde los más jóvenes suelen juzgar como creíble en primer lugar al internet.…”
Section: Discussionunclassified